Yield and Utility of Germline Testing Following Tumor Sequencing in Patients With Cancer - Stephen E. Lincoln; Robert L. Nussbaum; Allison W. Kurian; Sarah M. Nielsen; Kingshuk Das; Scott T. Michalski; Shan Yang; Nhu Ngo; Amie Blanco; Edward D. Esplin (2020)
Importance Both germline genetic testing and tumor DNA sequencing are increasingly used in cancer care. The indications for testing and utility of these 2 tests differ, and guidelines recommend that germline analysis follow tumor sequencing in certain patients to determine whether particular variants are of somatic or germline origin. Broad clinical experience with such follow-up testing has not yet been thoroughly described. Objective To examine the yield and utility of germline testing following tumor DNA sequencing in a large, diverse patient population. Design, Setting, and Participants A retrospective cohort study examined germline testing through a laboratory supporting multiple academic and community clinics. Participants included 2023 patients with cancer who received germline testing and previously underwent tumor DNA sequencing. These patients received germline testing between January 5, 2015, and January 31, 2020, although most (81% of patients) received testing between January 2, 2018, and January 31, 2020. Main Outcomes and Measures The prevalence of pathogenic germline variants (PGVs) was calculated by gene, cancer type, and age at diagnosis. Potential actionability of these findings was determined based on current management guidelines, precision therapy labels, and clinical trial eligibility criteria. Patient records were reviewed to determine whether germline follow-up testing would have been recommended by current guidelines. Results Among 2023 eligible patients, 1085 were female (53.6%), and the median age at cancer diagnosis was 56 (range, 0-92) years. Pathogenic germline variants were detected in 617 patients (30.5%; 95% CI, 28.5%-32.6%) and were prevalent across patient ages (1-85 years) and cancer types, including cancers known to be strongly associated with germline variance (eg, breast, colorectal) as well as others (eg, renal, lung, and bladder). Many patients (78%-82%) with PGVs met criteria for germline follow-up testing, and 8.1% of PGVs were missed by tumor sequencing. Among those with germline-positive findings, 69 patients (11.2%) had PGVs identified only after presenting with a second primary cancer that possibly could have been detected earlier or prevented given current gene-specific surveillance and risk-reduction recommendations. Conclusions and Relevance The findings of this study suggest that germline analysis following tumor sequencing often produces findings that may impact patient care by influencing systemic therapy choices, surgical decisions, additional cancer screening, and genetic counseling in families. Current guidelines and tumor testing approaches appear to capture many, but not all, of these germline findings, reinforcing the utility of both expanded germline follow-up testing as well as germline analysis independent of tumor sequencing in appropriate patients.